Tattoo inks for optical biosensing in interstitial fluid - Pazos,MD; Hu,Y; Elani,Y; Browning,KL; Jiang,N; Yetisen,AK (Advanced Healthcare Materials, 2021)
The persistence of traditional tattoo inks presents an advantage for continuous andlong-term health monitoring in point of care devices. The replacement of tattoo pigments withoptical biosensors aims a promising alternative for monitoring blood biomarkers. Tattoo inksfunctionalization enables the control of interstitial biomarkers with correlated concentrations inplasma, to diagnose diseases, evaluate progression, and prevent complications associated withphysio pathological disorders or medication mismatches. The specific biomarkers in interstitialfluid provide a new source of information, especially for skin diseases. The study of tattoo inksdisplays insufficient regulation in their composition, a lack of reports of the relatedcomplications and a need for further studies on their degradation kinetics. This review focuseson tattoo optical biosensors for monitoring dermal interstitial biomarkers and discusses theyclinical advantages and main challenges for in vivo implantation. Tattoo functionalizationprovides a minimally invasive, reversible, biocompatible, real-time sensing with long-termpermanence and multiplexing capabilities for the control, diagnosis, and prevention of illness;it enables self-controlling management by the patient, but also the possibility of sending therecords to the doctor.